Respuesta :
Answer:b=6 is the answer
Step-by-step explanation: Isolate the variable by dividing each side by factors that don't contain the variable.
Distribute
2b -1(3b-4) =-2
2b-3b+4=-2
Combine like terms
2b -3b+4=-2
-b+4=-2
Subtract 4 from both sides of the equation
-b+4=-2
-b+4-4=-2-4
Simplify
-b=-6
You supposed to subtract the numbers
Divide both sides of the equation by the same term
-b=-6
-b/-1=-6/-1
Simplify
Divide the numbers , cancel terms that are both the numerator and denominator
B=6
Solution b=6
2b -1(3b-4) =-2
2b-3b+4=-2
Combine like terms
2b -3b+4=-2
-b+4=-2
Subtract 4 from both sides of the equation
-b+4=-2
-b+4-4=-2-4
Simplify
-b=-6
You supposed to subtract the numbers
Divide both sides of the equation by the same term
-b=-6
-b/-1=-6/-1
Simplify
Divide the numbers , cancel terms that are both the numerator and denominator
B=6
Solution b=6